KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA PARIAMAN - Anggi Luthfia (Jurnal Bahana Manajemen Pendidikan, 2014)
Abstract The goal of this research are to see information about  the performance of servants. The population is 38 servant. This research is a research of population because subject <100 person. The instrument of this research is question with Likert scale models  that had tested for validity and reliability. Data analyzed using mean score. The result of this research are the performance of public servants at Dinas Pendidikan Pemuda dan Olahraga Pariaman City stay in quite accomplished category. Key word : The performance of servants